Global Mental Health: challenges for a global ethics - Lolas Stepke, Fernando (Acta Bioethica, 2016)
This paper aims at presenting a perspective on a global ethics useful for conducting and evaluating research on global mental health. It includes the proposal of expanding the scope of “global” to include different aspects of cultural diversity and a plea for a “differential ethics” approach that accepts diversity and sociocultural determinants of health. The contention is advanced that ethics is a linguistic justification of moral norms based on customs, beliefs, and traditions. Besides its foundation on rational or religious beliefs, ethics should also be conceived of as a way of attaining human fulfillment of interests and expectations in the context of different forms of humanity.